Cost-effectiveness of adrenaline for out-of-hospital cardiac arrest - Achana, F; Petrou, S; Madan, J; Khan, K; Ji, C; Hossain, A; Lall, R; Slowther, A-M; Deakin, CD; Quinn, T; Nolan, JP; Pocock, H; et al. (BioMed Central, 2020)
Background The ‘Prehospital Assessment of the Role of Adrenaline: Measuring the Effectiveness of Drug Administration In Cardiac Arrest’ (PARAMEDIC2) trial showed that adrenaline improves overall survival, but not neurological outcomes. We sought to determine the within-trial and lifetime health and social care costs and benefits associated with adrenaline, including secondary benefits from organ donation.